Mengeksplorasi Keanekaragaman Mikroalga di Indonesia: Memanfaatkan Potensi Bioremediasi Timbal - Andriani, Feni; Hendrayanti, Dian; Yasman, Yasman (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Indonesia's biodiverse microalgae, numbering 2060 species, thrive in diverse environments, offering potential in pharmaceuticals, cosmetics, fuel, and heavy metal bioremediation. Lead pollution from mining poses risks, prompting stringent government contamination limits. Microalgae-based bioremediation, notably Chlamydomonas reinhardtii and Chlorella vulgaris removing up to 90% of lead, suggests further exploring Indonesia's microalgae diversity. Methods: Data sourcing (2013-2023) employed Google and Google Scholar using specific keyword combinations across Indonesian provinces. Seventy-eight sources underwent analysis and visualization via Microsoft Excel 2021. Results: Microalgae's potential as lead bioremediation was explored across classes like Chlorophyceae, Cyanophyceae, and Bacillariophyceae. Chlorophyceae, exemplified by Chlorella and Scenedesmus, exhibit varied cell sizes and complex cell walls, aiding metal ion binding. Cyanophyceae like Cyanospira capsulata and N. commune synthesize diverse EPS compositions, indicating their potential in lead remediation. Conclusions: Indonesia's microalgae diversity across habitats, especially in the Chlorophyceae and Cyanophyceae classes, suggests a significant role in lead bioremediation. Their adaptability and diverse compositions highlight their potential for sustainable practices in combatting environmental lead contamination.